Practical code generation in .NET covering Visual Studio 2005, 2008, and 2010 - Vogel, Peter 1953- (Addison-Wesley, 2010)
"Once this skill is within your everyday comfort zone, it will give your productivity a boost and increase your value to your team. I encourage you to add the techniques outlined in this book to your toolset and to use them to develop your own workbench of generative tools. In doing so, I'm confident you'll improve your capabilities, and what's more, have fun doing so."--The Foreword by Gareth Jones, Developer Architect, Visual Studio ®, Microsoft Enlist Visual Studio's Built-in Code Generation Tools to Write Better Software Faster Automatic code generation can dramatically increase your productivity, improve code quality and maintainability, promote reuse, and help you extend best practices throughout your development organization. .NET and Visual Studio contain many powerful, code-generation tools--and this book shows you how to succeed with all of them. With Practical Code Generation in .NET, spend less time writing monotonous, repetitive code--leaving more time to address troublesome areas! Microsoft MVP Peter Vogel covers code generation with Visual Studio 2010, 2008, and 2005, as well as all recent versions of .NET, including .NET 4.0. You'll learn when enlisting code generation makes sense and how to design solutions that build on the skills and resources you already have. Writing for experienced programmers, Vogel shows how to generate reliable code using procedural code, Visual Studio add-ins, XML, configuration files, and more--including Microsoft's innovative CodeDOM technology for generating code in multiple languages. He brings everything together in three complete, chapter-length case studies. Coverage includes - Understanding the structure of .NET code-generation solutions and best practices for architecting them - Creating Visual Studio add-ins that quickly integrate code generation into day-to-day activities - Using objects and methods to add or remove project components - Using text insertion to generate code using any tool--even standard string handling functions - Working with the specific features of C#, Visual Basic .NET, and ASP.NET - Generating more concise code with .NET's new Text Template Transformation Toolkit (T4) - Building code-generation solutions with Visual Studio templates, attributes, and custom tools - Distributing code-generation solutions.
Includes bibliographical references and index. - Print version record
Keywords: Microsoft Visual studio; Microsoft .NET Framework; Code generators; Générateurs de codes